Pengembangan Ekosistem Pertanian Berkelanjutan Melalui Literasi Keuangan dan Pelatihan Pupuk Organik Cair pada Komunitas Petani Kawasan Transmigrasi Selaparang, Lombok Timur, Nusa Tenggara Barat - Pranata, Rici Tri Harpin; Fadilah, Umi Nurul; Al-Azhari, Lalu Muh Fathul Aziz; Silalahi, Yolanda Anggraini; Hutahaean, Bima Yeremia (Abdimas Mandalika, 2026)
Abstract:  The paradigm of transmigration area development has shifted from a population relocation approach to an effort to empower communities by strengthening their socio-economic capacities. In this context, this activity focuses on enhancing the economic institutional capacity of farmers through two main types of training: financial literacy training and liquid organic fertilizer (LOF) production training. The activity was conducted in the Selaparang Transmigration Area, East Lombok, which covers three sub-districts and 23 villages. Training needs were formulated based on data gathered through focus group discussions (FGD), in-depth interviews, and field observations, which revealed that farmers still face challenges in recording farm finances and have a high dependence on chemical fertilizers. The training methods were designed to improve farmers’ abilities in financial record-keeping, farm business planning, and local-material-based LOF production as a more environmentally friendly and economical alternative. The results of the activity showed an increase in farmers’ understanding and skills in managing institutional finances more accountably, as well as the ability to independently produce LOF. Both trainings contributed to strengthening farmers’ institutions and served as an initial step in supporting the independence and sustainability of farming businesses in the transmigration area.Abstrak: Paradigma pembangunan kawasan transmigrasi mengalami perubahan dari pendekatan pemindahan penduduk menjadi upaya pemberdayaan masyarakat melalui penguatan kapasitas sosial-ekonomi. Dalam konteks tersebut, kegiatan ini berfokus pada peningkatan kapasitas kelembagaan ekonomi petani melalui dua bentuk pelatihan utama, yaitu pelatihan literasi keuangan dan pelatihan pembuatan pupuk organik cair (POC). Kegiatan ini dilaksanakan di Kawasan Transmigrasi Selaparang, Lombok Timur, yang mencakup tiga kecamatan dan 23 desa. Kebutuhan pelatihan dirumuskan berdasarkan hasil penggalian data melalui focus group discussion (FGD), wawancara mendalam, dan observasi lapangan yang mengungkap bahwa petani masih menghadapi permasalahan dalam pencatatan keuangan usaha tani serta tingginya ketergantungan pada pupuk kimia. Metode pelatihan dirancang untuk memperkuat kemampuan petani dalam pencatatan keuangan, perencanaan usaha tani, serta produksi POC berbahan baku lokal sebagai alternatif yang lebih ramah lingkungan dan ekonomis. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan keterampilan petani dalam mengelola keuangan kelembagaan secara lebih akuntabel, serta kemampuan untuk memproduksi POC secara mandiri. Kedua pelatihan ini berkontribusi pada penguatan kelembagaan petani dan menjadi langkah awal dalam mendukung kemandirian serta keberlanjutan usaha tani di kawasan transmigrasi.